The Application of the Picture and Picture Model in Learning to Write Explanatory Texts for Class VIII Students at SMP NU Kaplongan in the 2023/2024 Academic Year - Carinih, Carinih; Tobroni, Tobroni; Naufal, Muji Zain (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
The objective of this research is to investigate the impact of using the Picture and Picture teaching method on the writing skills of eighth-grade students at SMP NU Kaplongan during the 2023/2024 academic year. This study employed an experimental design with two groups: an experimental class that used the Picture and Picture model and a control class that did not. The research subjects consisted of 35 students from class VIII E (experimental class) and 35 students from class VIII F (control class). Data were collected through a writing test that measured the ability to write explanatory texts based on four assessment aspects: theme, general statement, cause-and-effect sequence, and interpretation. The results showed that the mean score of the experimental class (81.24) was significantly higher than that of the control class (68.45). This indicates that the application of the Picture and Picture model can improve students' explanatory text writing skills. Additionally, the highest-performing assessment aspect was theme (96.36), while the interpretation aspect had the lowest average score (67.87). Based on the findings, it is recommended that school principals encourage Indonesian language teachers to adopt the Picture and Picture method as an alternative approach to teaching explanatory text writing. Furthermore, future research should explore other aspects of writing instruction using this method.